One-Step Pharmaceutical Preparation of PEG-Modified Exosomes Encapsulating Anti-Cancer Drugs by a High-Pressure Homogenization Technique - Tatsuya Fukuta; Mayumi Ikeda-Imafuku; Satoshi Kodama; Junko Kuse; Ko Matsui; Yasunori Iwao (MDPI AG, 2023)
The use of exosomes encapsulating therapeutic agents for the treatment of diseases is of increasing interest. However, some concerns such as limited efficiency and scalability of conventional drug encapsulation methods to exosomes have still remained; thus, a new approach that enables encapsulation of therapeutic agents with superior efficiency and scalability is required. Herein, we used RAW264 macrophage cell-derived exosomes (RAW-Exos) and demonstrated that high-pressure homogenization (HPH) using a microfluidizer decreased their particle size without changing their morphology, the amount of exosomal marker proteins, and cellular uptake efficiency into RAW264 and colon-26 cancer cells. Moreover, HPH allowed for modification of polyethylene glycol (PEG)-conjugated lipids onto RAW-Exos, as well as encapsulation of the anti-cancer agent doxorubicin. Importantly, the doxorubicin encapsulation efficiency became higher upon increasing the process pressure and simultaneous HPH with PEG-lipids. Moreover, treatment with PEG-modified RAW-Exos encapsulating doxorubicin significantly suppressed tumor growth in colon-26-bearing mice. Taken together, these results suggest that HPH using a microfluidizer could be useful to prepare PEG-modified Exos encapsulating anti-cancer drugs via a one-step pharmaceutical process, and that the prepared functional Exos could be applied for the treatment of cancer in vivo.